Islam, Christianity, and the Formation of Secularism in Indonesia 1945-1960 - Alexander Arifianto (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2022)
In this article, I will apply the varieties of secularism theory developed by Elizabeth Shakman Hurd and Ahmet Kuru in the case of Indonesia. Following Kuru’s typology, I argue that Indonesian secularism resembles that of passive secularism. This form of secularism came about from an alliance between secular nationalists and a religious minority (Christianity). The alliance between the two groups had successfully prevented Islam from becoming a dominant religion when an independent Indonesian state was formed in 1945. It was also successful from preventing reformist Muslims from instituting a state based on the sharia law during the crucial period of state-building in Indonesia between 1945 and 1960. However, this alliance also results in the formation of two authoritarian regimes that ruled Indonesia for four decades (1959-1998), and in the often tenuous relationship between two religious groups that sat on the opposite end of this conflict, namely Indonesian Muslims and Christians.